Methodology of the Modular ECG Analysis System MEANS - van Bemmel, J. H.; Kors, J. A.; van Herpen, G. (Methods of Information in Medicine, 1990)
The methodology, used in the Modular ECG Analysis System (MEANS) is described. MEANS consists of modules for signal analysis and diagnostic classification. The basic structure of the modular interpretation system remained intact over a period of 20 years, while all modules underwent many changes as a function of experience and insight, and the continuously changing information technology. The article describes the advantages of a modular approach to decision-support systems, the most important ones being easier maintenance of the software package and separate optimization and testing of each module. The overall evaluation of MEANS was done in the CSE study. Evaluation results for modules and for the entire system are presented.
Keywords: ECG; VCG; Computer-Assisted Interpretation; Signal Analysis; Classification; Evaluation